(3bWYI ef cJGH aj GdHdGZIs - (3VjGA GdOjf CHh fUQ GdaJM Hf fUQ Gddg Hf eMeO Hf YHO GdcQje GdeYQha HGHf GdCKjQs ((3OeTb GdeMQhSI s)
(3ChdgG (B:s
(3MQha Gdfai EPG JbOe Ydi cd daXkG Ch JbOjQkG aGdeYfi Ydi fai GdTehd Ohf fai GdaYd s
(3BNQgG (B:s
(3agPG HjGf EfbSGe GdYdhe efg hJTYHgG Ydi CeQ cdi hdh CNP ai TQM JaGUjdgG VGb GdeLGd hGJSY GdebGd hgPG BNQ GdcJGH hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3MGdI GdfSNI LjOI s
Keywords: (3GdHdGZIs